Non-porous ceramic-metal composite material and method for making the same
By using a vacuum pressure conversion furnace in the manufacturing process of ceramic-metal composite materials, the problem of pores generated in composite materials during processing is solved, and the density and performance of the material are significantly improved.
Patent Information
- Application Number
- CN202180050156.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-14
- Filing Date
- 2021-08-05
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2041-08-05
AI Technical Summary
Aluminum-containing ceramic-metal composites are prone to pores during processing, resulting in a decline in material properties, especially the strength is negatively affected.
A vacuum pressure conversion furnace (VPT furnace) is used to carry out the displacement reaction, and by applying negative pressure and positive pressure of inert gas, the pores in the composite material can be significantly reduced or eliminated.
It effectively eliminates the centerline pores in ceramic-metal composite materials and improves the density and performance of the material, especially the strength.
Smart Images

Figure CN116096687B_ABST
Abstract
Description
Background Art
[0001] The present invention includes embodiments of non-porous ceramic-metal composites and methods of making the same. Ceramic-metal composites, particularly those including aluminum and aluminum compounds as constituent components, have many applications. These include use in brake components, including brake rotors, degassing rotors, risers, dies and molds, heater dip tubes, thermocouple protection tubes, ladles, stirring devices, bearings, nozzles, bushings, valve components, clutches, engine components, turbine components, electrical conductors, radiators, heat diffusers, metalworking dies, cutting tools, components for sporting goods, such as golf club heads and skate blades, impellers, and the like.
[0002] However, the applicant has found that aluminum-containing ceramic-metal composites have an inherent problem of porosity generated during processing. Such porosity has a significant negative impact on the properties of the composite material, especially its strength, which limits the practical use of the material. Therefore, an important object of the present invention is to significantly reduce or eliminate porosity, thereby increasing density and improving material properties.
[0003] As described in more detail below, this objective is achieved by manufacturing ceramic-metal composites in which the porosity is significantly reduced (and the density is significantly increased) by using special equipment that applies negative pressure (also known as a vacuum) and positive pressure of an inert gas to reduce or eliminate the porosity in the final composite.
[0004] The embodiments of the present invention are improvements to the inventions described in U.S. Pat. Nos. 5,214,011, 5,728,638, and 7,267,882. The preferred embodiments from these three prior art patents involve the following two main process steps:
[0005] 1. A preform shape containing a sacrificial oxide ceramic, typically silicon dioxide (SiO2), is typically manufactured. The preform shape may consist entirely of the sacrificial oxide, or may also include an inert ceramic additive, typically silicon carbide (SiC). Additionally, the preform shape may be porous, or it may be completely solid with no internal void spaces (also called pores).
[0006] 2. The preform shape is preheated in one furnace to an operating temperature typically between about 1000 and 1250°C and then completely immersed in a bath of liquid aluminum (Al) that has been maintained in a second furnace within the same temperature range and then finally extracted from the bath after the treatment is completed. The resulting shape retains the original dimensions of the preform shape, but during the immersion process, the preform material is transformed into a ceramic-metal composite. The aluminum bath can be pure, or it can contain trace impurities, inert alloying elements, or (when SiC is present in the preform) 20 to 30 weight percent silicon (Si) to completely inhibit any reaction between SiC and Al. The second furnace includes a lower part that contains the liquid aluminum and a top part that contains the heating system; the top part is removed when it is necessary to immerse or extract the shape from the bath. An inert gas (such as argon) flows into the furnace at atmospheric pressure to protect the liquid aluminum from excessive oxidation. When the preform is immersed, the sacrificial oxide reacts with the aluminum through a replacement reaction. The following reaction occurs when silicon dioxide is used: 4Al+3SiO 2 =2Al 2 O 3 +3Si. The shape is kept in the liquid aluminum bath long enough for the replacement reaction to be completed and all the sacrificial oxide to be converted to aluminum oxide (Al 2 O 3 ). After the reaction is complete, the shape is removed from the liquid aluminum bath. If there was no silicon in the bath initially, the silicon produced by this reaction will be significantly diluted, producing Al 2 O 3 -Al composites. If the preform contains silicon carbide, Al 2 O 3 -Al-Si-SiC composites. If the starting preform shape contains internal void space, the weight of aluminum and silicon in the final composite will depend on the amount of porosity in the original preform and the extent to which the void space is filled with aluminum alloy during processing.
[0007] At present, the applicant uses this preferred embodiment to manufacture The applicant also uses the term "conversion process" to describe its manufacturing method which involves a replacement reaction in a liquid metal bath.
[0008] In addition to producing unique materials with useful properties, this conversion process also has the ability to produce net or near-net useful shapes, which provides economic advantages over other competing processes. The conversion process retains these characteristics by using common manufacturing techniques to manufacture the preform into a net shape, thereby eliminating or significantly reducing any cutting or grinding required to utilize the final shape. Therefore, these ceramic-metal composites produced by this prior art have a variety of useful properties and can be formed into net or near-net useful shapes for a variety of applications. However, material defects in the final composite, such as voids (measured as pores), will limit these properties, and the larger the pores, the more negatively affected the properties are. Applicants have discovered that following the preferred embodiments of the three prior art patents will consistently result in pores concentrated in the central region of the ceramic-metal shape. Due to its use in e.g. Figure 1 This is more commonly referred to as centerline porosity because of the way it appears on the cross-section sample shown. Further investigation revealed that this porosity is concentrated in the free aluminum phase of the composite.
[0009] The present invention is the result of research into the root causes of porosity in these ceramic-metal composite shapes and the development of new processing methods to eliminate these defects, thereby maximizing performance. Centerline porosity was determined to be caused by a combination of three factors: 1) dissolved hydrogen; 2) shrinkage of the liquid aluminum during solidification; and 3) how heat is removed from the composite shape after it is extracted from the aluminum bath at the end of the transformation process. As the liquid aluminum solidifies, it undergoes considerable shrinkage while hydrogen is expelled, both of which create porosity in the solid aluminum phase. The third factor is a direct result of how the preferred embodiments from the three prior art patents were implemented: the outer surfaces of the composite shape are cooled first and the center portion is cooled last, which concentrates the shrinkage and gas porosity in the center, forming centerline porosity.
[0010] Hydrogen is highly soluble in liquid aluminum. The main source of hydrogen is the reaction of moisture in the air with liquid aluminum through the following reaction: 3H 2 O+2Al=Al 2 O 3+6H. This phenomenon occurs in pure aluminum as well as aluminum alloyed with other components. The solubility of hydrogen increases with the temperature of aluminum: for example, the solubility of hydrogen in liquid pure aluminum at 660°C is 0.65 mL of hydrogen per 100 grams of aluminum, while at 900°C it is 3 mL / 100 grams. In addition, the solubility of hydrogen in pure aluminum drops significantly as the metal solidifies: at 660°C, the solubility in liquid aluminum is 0.65 mL / 100 g, but when the aluminum solidifies, it is only 0.034 mL / 100 g. Hydrogen is then expelled from the liquid aluminum as it cools, and then pores are created as the metal solidifies. The pores created by dissolved hydrogen have a great impact on the mechanical properties of aluminum. As an example, a 356 aluminum alloy containing about 0 dissolved hydrogen will have a tensile strength of 41,000 psi, while the same alloy containing 0.27 mL / 100 g of dissolved hydrogen when cast will have a strength of 35,000 psi, a 15% loss.
[0011] The problems associated with the solubility of hydrogen in liquid aluminum, the subsequent porosity created in the solid aluminum, and techniques to mitigate or eliminate such porosity are well documented in the prior art. In the field of aluminum and aluminum alloy metal casting, a variety of techniques are used throughout the industry. Gas purging is the most widely used technique, where an inert gas (e.g., argon) or an inert reactive gas mixture (e.g., argon + chlorine) is bubbled through the liquid aluminum and the dissolved hydrogen is expelled from the liquid. Applying a vacuum to the liquid aluminum is also known, but it is not used to a great extent by metal casting manufacturers.
[0012] The second source of porosity in ceramic-metal composites is caused by shrinkage during solidification, and the effects of this type of porosity are much more significant than those caused by dissolved hydrogen. After cooling and solidification of liquid aluminum and aluminum alloys, the material density increases significantly; in other words, as the liquid solidifies, the volume decreases significantly, also known as shrinkage. If this shrinkage is not compensated during solidification, the solid metal will contain porosity. Most of the volume shrinkage occurs at the melting point: the melting point of pure aluminum is 660°C, and when liquid aluminum solidifies at this temperature, the density increases from 2.368 g / cm3 to 2.548 g / cm3, which results in a volume shrinkage of 7.1%. Aluminum alloys also experience volume shrinkage during solidification: depending on the alloying elements, the volume shrinkage can range from 3.5 to 8.5%. Again, if the volume shrinkage is not backfilled with more aluminum, this will result in an equal amount of porosity. If the porosity is severe enough, the mechanical properties of the solid metal will be negatively affected. As an example, when porosity in 319 aluminum casting alloy increases from approximately 0% by volume to 5% by volume, the tensile strength decreases by more than 50% (from 225,000 psi to less than 100,000 psi) and the metal becomes more brittle.
[0013] The phenomenon of shrinkage porosity in aluminum and aluminum alloy castings is also well documented in the prior art.The primary technique for reducing or eliminating porosity in aluminum castings is through the use of risers.
[0014] Metal castings are produced by pouring liquid metal into a mold, with risers being reservoirs for liquid designed to solidify last after the casting has fully solidified in the mold; as the liquid metal in the mold cavity solidifies and shrinks, liquid is drawn from the risers to compensate for the shrinkage. Other techniques utilize mold materials and designs that affect the way the liquid metal solidifies within the mold to eliminate porosity caused by solidification shrinkage. However, these techniques are not practical for ceramic-metal composites produced by following the preferred embodiments of the prior art patents because the method does not use any type of mold when performing the replacement reaction.
[0015] Finally, the location of the shrinkage porosity is a direct result of following the preferred embodiments of the three prior art patents. As previously described, a preform shape containing a sacrificial oxide ceramic is fully immersed in a liquid aluminum bath maintained at approximately 1000 to 1250°C, and after the replacement reaction is complete, the shape is extracted from the bath. Initially, the final ceramic-metal composite shape emerges from the bath at a uniform temperature equal to the temperature of the liquid aluminum bath, but the outer surface immediately begins to cool. Because the shape is free-standing, residual heat is continuously dissipated from the outer surface and a temperature gradient is created whereby the area closest to the outer surface is cooler than the area located in the center of the shape. As the temperature drops to the aluminum solidification temperature (e.g., 660°C for pure aluminum and 577°C for aluminum-silicon alloys), the aluminum in the area closest to the outer surface will solidify first, and the subsequent shrinkage will be backfilled by the liquid aluminum in the center of the shape. This will continue as cooling proceeds until all of the aluminum in the composite shape is completely solidified. However, centerline porosity has already been formed because it is the last area of aluminum to solidify and there is no ability to backfill the porosity with additional aluminum. As an example, Figure 1 Shown are centerline apertures formed in test bars processed by following preferred embodiments from three prior art patents.
[0016] The applicant is aware of the following prior art:
[0017] The Lanxide™ Ceramic Composites Formation by Newkirk et al. (Journal of Materials Research, Vol. 1, No. 1, February 1986, pp. 81-89) describes the Lanxide DIMOX (Directed Metal Oxidation) process for preparing ceramic-metal composites. This manufacturing technique utilizes a gas phase transport process and involves oxidizing a bulk liquid metal by a gas to produce a ceramic-metal composite, such as aluminum oxide (Al2O3). 2 O 3 )-aluminum (Al) ceramic-metal composite materials.
[0018] US Patent #4,713,360 to Newkirk also discloses a preferred embodiment of the Lanxide DIMOX (Directed Metal Oxidation) process.
[0019] U.S. Patent No. 2,702,750 issued to George discloses a method for producing aluminum oxide (Al 2 O 3 The present invention relates to a method for producing a )-aluminum (Al) ceramic-metal composite material produced by a substitution reaction in a liquid metal Al bath at a preferred temperature of 700 to 900°C. The present invention differs from George's teaching in that the method of the present invention is carried out at a temperature significantly higher than George's temperature (typically 1000 to 1200°C). However, the composite material produced by following the preferred embodiments of this patent also suffers from centerline porosity due to aluminum shrinkage during solidification.
[0020] Breslin, U.S. Pat. No. 5,214,011, discloses a method for producing aluminum oxide (Al 2 O 3 The invention relates to a method for producing a ceramic-metal composite material of aluminum (Al) by a replacement reaction in a liquid metal bath at a preferred temperature at least 300°C above the melting point of aluminum (Al) (660°C). The method disclosed in the patent is carried out at 960°C and higher.
[0021] US Patent No. 5,728,638 to Strange discloses an improvement over the invention disclosed in Breslin's '011 patent by incorporating an inert metal additive which results in improved properties.
[0022] Breslin, US Patent No. 7,267,882 discloses an improvement to the invention disclosed in Breslin's '011 patent that results in improved properties by the introduction of an inert ceramic additive such as silicon carbide.
[0023] Breslin's '011 patent, Strange's '638 patent, and Breslin's '882 patent all discuss methods of making ceramic-metal composites using shapes containing sacrificial oxides (generally referred to as a transformation process). 2 O 3 -Al composite materials, while Breslin's 882 patent focuses on Al 2 O 3-Al-SiC composites, none of which recognize that the free aluminum or aluminum alloy in these composites has a strong tendency to form pores when the composites are processed, and that such pores are a significant limiting factor in how the composites can be used in high stress applications. Furthermore, by following the examples of these prior art patents, the resulting ceramic-metal composites will have centerline pores and subsequent negative effects on material properties as described above.
[0024] Co-continuous Al / Al 2 O 3 Liquid displacement reactions of composites produced: Relationship between microstructure and mechanical behavior, G.M. LaVecchia, C. Badini, F.D. Errico, 2003. These researchers conducted experiments on ceramic-metal composites produced by following the preferred embodiments of the Breslin patent No. 011, specifically, silica preforms (in the form of fused silica glass) were transformed in a liquid metal bath consisting of pure aluminum or an alloy of aluminum plus 10% silicon. In all samples, the researchers found that the final composites contained up to 1.7% (volume) of residual porosity. In addition, the researchers documented how this porosity negatively affected the mechanical properties of the composites, such as poor tensile strength, and also caused scatter in the test results. This reference documents the problems experienced by the applicant's assignee in implementing the preferred embodiments of the Breslin patent.
[0025] From Kyle Myers: Structure-Property Relationships of Ceramic-Metal Interpenetrating Phase Composites Fabricated from Binder Jetted Fused Silica Preforms, 2016. This researcher experimented with ceramic-metal composites that were fabricated by following the preferred embodiments of Breslin's '011 patent, specifically fabricating silica preforms by additive manufacturing (also known as 3D printing) and then transforming them in a bath of liquid metal consisting of pure aluminum. Porosity was found in all of the composite samples fabricated by the researcher, and he documented how this porosity negatively impacted physical properties such as strength and stiffness. An attempt was made to utilize hot isostatic pressing (HIP) as a post-processing technique, but this did not eliminate all porosity in the composite samples. The researcher also attempted to utilize vacuum and inert gas pressure (3.45 MPa) during the transformation process, but these samples still contained porosity. This reference documents that the applicant's assignee has experienced problems with executing the preferred embodiments of the Breslin patent, and also supports that utilizing vacuum and pressure to produce ceramic-metal composites without porosity is a patentable invention.
[0026] Co-continuous composites for friction and braking applications, G.S. Daehn and M. C. Breslin, 2006. These researchers experimented with ceramic-metal composites produced by following the preferred embodiments of Breslin's '011 patent and Breslin's '882 patent, specifically by making preforms containing silicon dioxide and silicon carbide and then converting them in a liquid metal bath consisting of aluminum and 25% silicon. Small samples were tested in a benchtop friction pair apparatus and the results showed that these ceramic-metal composites are potential lightweight materials for use as automotive brake rotors. However, applicant's assignee's experience is that by following the preferred embodiments of Breslin's '011 patent and Breslin's '882 patent, making full-size automotive brake rotors, and testing rotor samples in a dynamometer simulating automotive braking conditions, these automotive brake rotors failed the test because the physical properties were significantly reduced due to the porosity.
[0027] The following prior art all discloses data to support the applicant's claims regarding the improvements of the present invention:
[0028] ASM Specialty Handbook: Aluminum and Aluminum Alloys, JRDavis, 1993;
[0029] Metals Handbook Ninth Edition, Volume 15: Casting, DM Stefanescu, 1988;
[0030] Metals Handbook Desk Edition, HE Boyer, and TL Gall, 1985;
[0031] Microstructure Development During Metalcasting, J.E. Gruzleski, 2000; and
[0032] Using Partial Pressure in Vacuum Furnaces, D.H Herring, Industrial Heating magazine, November 2005.
[0033] These books and articles document the properties of aluminum and aluminum alloys, including the shrinkage of liquid aluminum as it solidifies, the solubility of hydrogen in liquid aluminum as it solidifies and how the gas forms pores, how pores negatively affect the properties of aluminum and aluminum alloys, and current techniques for heat treatment and vacuum processing. Summary of the invention
[0034] The present invention includes embodiments of non-porous ceramic-metal composites and methods of making the same. Ceramic-metal composites containing aluminum or aluminum alloys are materials with a variety of useful properties. However, by following the methods of the prior art, these composites will contain pores, which significantly reduce their performance and usefulness. The present invention includes the following objects, aspects and features:
[0035] (1) To solve this problem, the present invention contemplates utilizing a unique furnace system to perform a metathesis reaction to produce these ceramic-metal composites, specifically, alumina (Al 2 O 3 )-aluminum (Al) composite material or alumina (Al 2 O 3 )-aluminum (Al)-silicon carbide (SiC) composites are produced by a replacement reaction in a liquid metal bath. Several embodiments of the present invention utilize a unique reformer system that integrates a preheating system with a liquid metal bath maintained at a temperature of at least 900°C or higher, all contained within a chamber that can be fully evacuated and pressurized with an inert gas. This unique furnace system may be referred to as a vacuum pressure reformer or VPT furnace for short.
[0036] (2) These new methods are not obvious compared to the prior art reflected in the prior art discussed above, particularly the Bleslin and Strange patents, which applicant currently uses to manufacture products based on Ceramic-metal composites sold under the trademark .
[0037] (3) The substitution reaction between the metal and the sacrificial oxide will result in a composite material consisting of a co-continuous ceramic-metal phase, and these materials have unique properties. Applicants' preferred method is to use a silicon dioxide (SiO 2 ) and conduct these substitution reactions by completely immersing the preform in a bath of liquid aluminum; this method of conducting substitution reactions is known as a "conversion" process. In order to avoid starving the reaction, the bath preferably contains more liquid metal than the minimum required. Furthermore, the preform shape is maintained in the bath until all the sacrificial oxide has reacted.
[0038] (4) In one version of this method, the following reaction is used to produce alumina ceramic-aluminum metal (Al 2 O 3-Al) based composite materials:
[0039] (4+x)Al+3SiO 2 =2Al 2 O 3 +xAl+3[Si]Al
[0040] Note that the silicon (Si) byproduct dissolves into the liquid aluminum (Al); most of it flows into the aluminum bath, and some amount remains in the final composite. This results in a material with 74 wt% Al 2 O 3 , 26 wt% Al and trace amounts of Si reaction byproducts.
[0041] (5) In another form of this conversion process, silicon carbide (SiC) particles can be added to these Al 2 O 3 -Al-based composites to affect the final properties, for example, to increase the thermal shock resistance of the material. Under the correct processing conditions, the SiC additive is inert and does not participate in the replacement reaction. More specifically, to prevent SiC from reacting with Al, the liquid aluminum bath contains excess Si to inhibit the reaction 4Al+3SiC=Al 4 C 3 +3Si. Subsequently, the reaction can be written as:
[0042] (4+x)Al+3SiO 2 +y[Si]Al+zSiC=2Al 2 O 3 +xAl+(3+y)[Si]Al+zSiC
[0043] (6) The obtained material retains the basic Al 2 O 3 -Al structure, which binds the SiC additive together. Regardless of whether the composite contains silicon carbide or not, the transformation process is carried out at temperatures generally above 900°C to form alpha alumina (αAlO) from a substitution reaction. Again, the resulting shape retains the original dimensions of the preform shape, but during infusion, the preform material is transformed into a ceramic-metal composite. Finally, all of these types of ceramic-metal composites are commercially produced by applicant's assignee, Fireline, Inc., and are manufactured according to Trademark for sale.
[0044] (7) As previously discussed, preferred embodiments from Breslin's '011 patent, Strange's '638 patent, and Breslin's '882 patent utilize a preheating furnace and a separate conversion furnace containing liquid aluminum. The preform shape is preheated in the first furnace to an operating temperature typically between about 1000 and 1250°C and then fully immersed in a bath of liquid aluminum (Al) that has been maintained in a second furnace within the same temperature range and then ultimately extracted from the bath after processing is complete. The second furnace includes a lower portion that contains the liquid aluminum and a top portion that contains a heating system; the top portion is removed when it is desired to immerse or extract the shape from the bath. An inert blanket gas (e.g., argon at atmospheric pressure) flows into the furnace to protect the liquid aluminum from excessive oxidation. Although the liquid aluminum bath can be degassed using conventional techniques described in the prior art to minimize any hydrogen porosity, centerline porosity can still form due to the manner in which the composite shape cools after being extracted from the liquid metal bath. The vacuum pressure reformer is a unique furnace system that solves both of these problems, resulting in a ceramic-metal composite that is essentially free of porosity and has optimal properties.
[0045] (8) Figure 2 and Figure 4 The composite material is shown running through the vacuum pressure reformer and does not show centerline porosity, but Figure 1 and Figure 3 A sample processed by following the prior art is shown and shows centerline porosity.
[0046] (9) As previously mentioned, the preferred embodiments from Breslin's '011 patent, Strange's '638 patent, and Breslin's '882 patent utilize two separate furnace systems: the first is used to preheat the preform shape to an operating temperature typically between about 1000 and 1250°C, while the second furnace consists of a lower portion that maintains the liquid aluminum within the same temperature range and a top portion that contains the heating system; the top portion is removed when it is desired to dip or extract the shape from the bath. An inert blanket gas (e.g., argon at atmospheric pressure) flows into the furnace to protect the liquid aluminum from excessive oxidation.
[0047] (10) The VPT furnace system is an improvement over these prior art furnace systems for a number of reasons: the shape preheating and conversion steps are performed in one furnace system rather than in two separate furnace systems; the use of vacuum pressure to remove air and moisture is much more effective than using an inert blanket gas, which significantly increases the cleanliness of the liquid metal bath; and the use of positive inert gas pressure eliminates the formation of centerline voids in the final composite shape.
[0048] (11) In addition, another benefit of the vacuum pressure reformer was surprisingly discovered: significantly higher reforming reaction rates were achieved compared to the prior art. Breslin's '011 patent, Strange's '638 patent, and Breslin's '882 patent all disclose reaction rates of 1 to 3 mm / hr achieved by following the preferred embodiments of these patents. For the same preform composition, the present invention unexpectedly achieves an improvement of 8.5 mm / hr or more, almost a three-fold improvement. As a result, utilizing a vacuum pressure reformer as a manufacturing process has significant advantages in that shape production rates can be three times faster than the prior art.
[0049] (12) Although prior art patents disclose how to use negative pressure and positive pressure in the processing of ceramic-metal composites, they do so differently from the disclosure of this application. For example, Breslin's 011 patent discloses the following at column 8, starting at line 52:
[0050] “Another advantage of the present invention is the ability to conduct the reaction in an oxygen-free environment (e.g., argon or Ar / H mixtures) or under full or partial vacuum. Thus, the present invention avoids undesirable side oxidation reactions that may occur in the Lanxide DIMOX process and other prior art processes.”
[0051] The disclosure by Breslin's '011 patent is purely for the purpose of contrasting the uniqueness of the present invention with other prior art techniques which require the presence of a substantial amount of an oxidizing atmosphere.
[0052] (13) In addition, Breslin's '882 patent discloses the following in column 4, beginning at line 17:
[0053] "The process has been successfully accomplished at pressures between 5 psig and 5 microns of mercury absolute above atmospheric pressure. The process has also been successfully accomplished in an inert atmosphere. It is believed that the method can also be successfully accomplished at higher pressures; and, as described below; the method and reaction do not rely on forcing liquid metal into the pores of the preform. Because the preform is preferably immersed in the liquid metal; there is no atmosphere surrounding the reaction other than the liquid metal.";
[0054] and starting at row 59 and column 5:
[0055] “Conventional composite preparation techniques often tend to increase porosity to enable the metal to flow into the preform and maximize contact with the ceramic matrix. Therefore, continuous porosity through the preform is required so there is a flow path without restrictive pressure, or pockets may be formed that the liquid metal cannot penetrate. These processes typically use positive or negative pressure to force the metal to flow into and through the pores. Unlike conventional composite formation, the aluminum in the present invention does not need to pass through the pores in the ceramic to contact the reactants. In the present invention, porosity in the preform is disadvantageous because the formation of the composite is reaction driven, not driven by the filling of the pores.
[0056] (14) These disclosures by Breslin's '882 patent are made to contrast the uniqueness of the invention with other prior art, in which the presence of pores in the preform is a requirement, while negative and / or positive pressure is utilized to force liquid metal into the pores of the preform in order to produce a ceramic-metal composite. Applicant agrees with Breslin's '011 patent, Strange's '638 patent, and Breslin's '882 patent that the preferred embodiments of the prior art do not require vacuum or pressure to carry out the replacement reaction; in the absence of vacuum or pressure, the transformation process can be successfully carried out on a solid or porous preform. However, these prior art patents do not recognize how the formation of pores in the final ceramic-metal composite is inherently a part of those preferred embodiments; the present application provides a unique solution to this problem.
[0057] Many potential industrial uses for these improved ceramic-metal composites are outlined in the prior art patents disclosed and discussed above. Current product and market development focus of applicant's assignee, Fireline, Inc., is on automotive brake rotors, and the composites of the present invention provide significant performance improvements in this application.
[0058] Therefore, a first object of the present invention is to provide a ceramic-metal composite material having no pores and a method for preparing the same.
[0059] It is another object of the present invention to provide a composite material that recognizes that the strength of the composite material is reduced when voids are present in the material.
[0060] Another object of the present invention is to lead to improvements in ceramic-metal composites, specifically those incorporating alumina and aluminum produced by substitution reactions in a liquid metal bath, by utilizing a unique furnace known as a vacuum pressure reformer.
[0061] It is another object of the present invention not only to provide such a composite material, but also to disclose and claim a method for making the same.
[0062] These and other objects, aspects and features of the present invention will be better understood from the following detailed description of the preferred embodiments, when read in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 is an optical photograph at 5X magnification of a prior art cross-sectioned test bar showing the centerline void.
[0064] Figure 2 is an optical photograph at 5X magnification of a cross-sectioned test bar made in accordance with the teachings of the present invention, showing the absence of centerline voids.
[0065] Figure 3 An optical photograph at 5X magnification of a prior art fracture test bar showing the centerline void.
[0066] Figure 4 is an optical photograph at 5X magnification of a fracture test bar made in accordance with the teachings of the present invention, showing the absence of a centerline void.
[0067] Figure 5 is a cross-sectional view of a vacuum pressure reformer with a shape actuator, with the shape in the preheat position.
[0068] Figure 6 is a cross-sectional view of a vacuum pressure reformer with actuators, the shape of which is immersed in liquid metal.
[0069] Figure 7 is a cross-sectional view of a vacuum pressure reformer without actuators, and its shape is in the preheating position on top of the solid metal.
[0070] Figure 8 is a cross-sectional view of a vacuum pressure reformer without actuators, the shape of which is immersed in liquid metal.
[0071] Fig. 9 is a cross-sectional view of a vacuum pressure converter without actuators, the shape of which has been subjected to a remelting-repressurization process cycle. DETAILED DESCRIPTION
[0072] The vacuum-pressure-transformation furnace is designed to carry out the transformation process and operates under two primary pressure conditions, either under negative pressure (i.e. vacuum) or under positive pressure, and uses both modes during the entire furnace cycle. At the beginning and end of each furnace cycle, when opened to form loading and unloading shapes, the furnace chamber is allowed to reach ambient atmospheric pressure. Figure 5 An example of a vacuum pressure reformer is shown in FIG, where the subcomponents are labeled:
[0073] A chamber system 10 capable of withstanding negative pressure and positive pressure of inert gas while operating at high temperature;
[0074] a chamber cover 11 or door that allows the crucible, metal charge, fixtures, and preforms or composite shapes to be inserted into or removed from the chamber;
[0075] a heating system 13 , which is integrated with the chamber and is capable of heating the metal to a liquid state and then to a temperature of at least 900° C. or more and of preheating the preform shape before immersion in the liquid metal bath;
[0076] Crucible 15, containing metal 17 for the conversion process; vacuum pump system 19;
[0077] an inert gas source and pressurization system 21;
[0078] Fixtures 23 for fixing the preform / composite shape 25 during processing.
[0079] Finally, an optional actuator mechanism 27 is used to fully immerse the preform shape into the liquid metal bath and extract the ceramic-metal composite shape from the liquid metal bath.
[0080] While the exact configuration of the VPT furnace may vary, it is this combination of characteristics that will enable the successful fabrication of ceramic-metal composites without porosity.
[0081] Vacuum pressure reformers are designed to achieve specified levels of vacuum pressure (as low as possible) and positive inert gas pressure (as high as possible), but the exact values used during processing will be determined by a number of factors, as described below.
[0082] A perfect vacuum is defined as a volume of space completely devoid of matter, with industrial applications utilizing partial vacuums where some matter is still present. In addition, it makes more sense to define the quality of a vacuum by how close it is to a perfect vacuum, measured in partial pressures (less than atmospheric pressure) in torr. At standard atmospheric pressure of 760 torr, the qualities of a vacuum are usually grouped as follows: low vacuum (760 to 25 torr), medium vacuum (25 to 0.001 torr), high vacuum (1x10 -3 Up to 1x10 -9 Torr), and ultra-high vacuum (1x10 -9 Up to 1x10 -12Torr). Applying a vacuum during the initial stages of a vacuum pressure reformer cycle has three benefits. The first is to remove moisture from the chamber, which significantly reduces the amount of dissolved hydrogen in the liquid aluminum. The second is to remove oxygen from the chamber; oxygen from air and humidity causes an oxide layer to form on the top surface of the liquid aluminum bath. This oxide layer, also known in the art as dross, forms a tough skin on the top surface of the melt that increases in thickness with increasing temperature and oxygen exposure time. As the preform shape is immersed in the liquid bath, the oxide layer is broken down and fragments may adhere to the outside of the shape or penetrate into the shape, both of which can cause potential quality issues in the final product. Using a vacuum reduces this oxide layer to a minimal thickness. The third benefit is to evacuate oxygen and moisture from the surface of the preform shape as well as from the pores within the material, eliminating another potential source of hydrogen or oxide defects. Thus, optimizing the use of vacuum during the initial stages of the vacuum pressure reformer cycle substantially eliminates the formation of hydrogen porosity and dross defects in the final ceramic-metal composite, and these results are typically achieved by utilizing medium (25 to 0.001 torr) or high vacuum (1×10 -3 1×10 -9 torr). The above three advantages can be achieved when a vacuum is applied in a VPT furnace when the system is at a lower temperature, but there is a risk of exceeding the boiling point of the materials in the VPT furnace when the temperature rises to 900°C and above. For example, the boiling point of liquid aluminum at 760 torr is 2327°C, but when the vacuum pressure drops to 0.1 torr, the boiling point drops to 1123°C. In this embodiment, the VPT furnace cycle can be operated at temperatures below 900°C using a vacuum such as 1×10 -4 The VPT furnace is typically operated at a high vacuum of 5 torr, but then reduced to a moderate vacuum, such as 5 torr, as the temperature increases above 900° C. Therefore, the boiling points of the materials contained within the VPT chamber must be carefully considered, as well as the vacuum level achieved during the VPT furnace cycle.
[0083] Finally, a benefit of applying a positive inert gas pressure during and after the shape is extracted from the liquid metal bath in the VPT furnace is to eliminate the formation of centerline porosity during the cooling of the shape. When a composite shape is extracted from a liquid metal bath, the outer surfaces cool first, and possibly faster than the inner regions. Therefore, the liquid metal located near the inner outer surfaces of the composite shape begins to solidify first. Centerline porosity forms because the central region of the composite shape is the last to solidify and there is no ability to backfill the porosity with additional liquid metal. By applying a positive inert gas pressure and controlling the cooling rate, the liquid metal within the composite shape solidifies more evenly while being pushed to the central region, thereby eliminating the possibility of having centerline porosity form. The present applicant has found that this benefit can be achieved at positive pressures of 0.3 MPa (50 psi) to 6.9 MPa (1000 psi) and higher.
[0084] like Figures 5 to 9 As shown, the vacuum pressure reformer can be configured to operate in two operating modes.
[0085] Figure 5 and Figure 6 The first mode shown achieves transformation of the preform shape by utilizing actuator 27. Using this mode, the entire process is performed in one furnace cycle, thereby producing a ceramic-metal composite material without centerline porosity.
[0086] Figure 7 , Figure 8 and Fig. 9 The second mode shown must be carried out in two furnace cycles. In the first cycle transformation of the preform shape 25, it is carried without an actuator, such as Figure 7 and 8 Then, a second cycle is performed, in which the same composite material shape 25 is subjected to a remelting-repressing process, as shown in FIG. Fig. 9 Remove the crucible 15 and the metal bath 17, and place the composite shape 25 back into the furnace chamber.
[0087] Both modes will result in composite shapes that do not contain centerline porosity. While the first vacuum pressure reformer furnace configuration mode appears to be the most convenient by performing the entire process in one furnace cycle, incorporating actuators in the system presents design and operational challenges as it must withstand both vacuum and high positive pressures at high temperature conditions. Therefore, operating the VPT furnace in the second configuration mode with two furnace cycles is an alternative.
[0088] In the case of the second configuration mode, the first furnace cycle is used to convert the preform material into a ceramic-metal composite without the use of an actuator. The composite shape remains in the liquid metal bath at the end of the conversion cycle and is then removed from the liquid under ambient pressure conditions. Even if the furnace cycle eliminates dissolved hydrogen by using vacuum pressure, centerline porosity will form due to the contraction of the liquid aluminum during solidification and the fact that the center area of the shape is the last to cool. Therefore, when the VPT furnace does not have an actuator, a second furnace cycle of remelting-repressurization treatment must be performed in order to eliminate the centerline porosity of the final composite shape.
[0089] During the second furnace cycle, the ceramic-metal composite shape is heated to a temperature just above the melting point of the metal component, with the furnace cycle starting with negative pressure to remove oxygen and moisture from the chamber and then switching to positive inert gas pressure to complete the cycle. The shape is heated to a high enough temperature and for a long enough time to melt the metal component of the composite. By applying positive inert gas pressure and controlling the cooling rate, the liquid metal inside is pushed to the center area while allowing the composite shape to solidify more evenly, eliminating the possibility of centerline porosity forming again. The properties of the ceramic-metal composite will be improved after the remelting-repressurization process.
[0090] The prior art definition of the term “heat treating” as defined by the Metals Handbook, Ninth Edition, is “the heating and cooling of a solid metal or alloy to obtain a desired condition or properties.” Additionally, the prior art process of “hot isostatic pressing” of solid aluminum alloys is conducted under high inert gas pressures but at below the initial melting temperature, as defined by the Metals Handbook, Ninth Edition, Volume 15: Casting. In both cases, these prior art methods require that the metal shape being processed remain solid and below the melting point. In contrast, the present invention’s use of a remelt-repressurize process is unique in that the process is specifically used to eliminate porosity in ceramic-metal composites by heating the material to the point where the metal components in the composite shape are melted and by applying negative and positive pressures.
[0091] The minimum processing temperature used in the remelt-repressurization furnace cycle will depend on the composition of the metal in the ceramic-metal composite, and more specifically, the melting point of the metal or metal alloy. For example, pure aluminum melts at 660°C, when aluminum is alloyed with magnesium, the initial melting point is 450°C, and when aluminum is alloyed with silicon, the initial melting point is 577°C. Therefore, the metal alloy composition in the ceramic-metal composite and the associated liquidus temperature need to be carefully considered.
[0092] The benefits found with vacuum pressure reformers are not possible using conventional reformers of the prior art. Eliminating the porosity in ceramic-metal composites by using a VPT furnace has a very significant impact on the final material properties. For example, similar to Figure 1 The test bars shown have a three-point flexural strength of 275 MPa or 39,900 psi (according to ASTM procedure C 1161) and a porosity of 1.5% by volume as measured using the Archimedean principle (according to ASTM procedure C 20), although similar to Figure 2 The test bar shown has a three-point bend strength of 423 MPa or 61,400 psi and no measurable porosity. By eliminating centerline porosity using this unique furnace system, the increased density maximizes the strength of the composite.
[0093] The following two embodiments of the present invention significantly alter the final density of the ceramic-metal composites of the prior art embodiments, thereby producing unique composites having lower porosity and subsequent improved properties compared to those obtained in the prior art embodiments.
[0094] In a preferred embodiment, a vacuum pressure reformer incorporates an actuator to manipulate the preform shape during controlled immersion in a liquid metal bath and to extract the part from the bath after the reforming reaction is complete. The configuration of the actuator will vary depending on a combination of factors including desired complexity and cost, but its function will always be to constrain the shape during immersion and extraction from the liquid metal bath. When using this actuator, the VPT furnace cycle essentially consists of seven phases.
[0095] First stage: mounting the preform shape in a fixture, preparing the crucible containing the aluminum charge, loading all crucibles into the VPT furnace at ambient atmospheric pressure, and then closing the chamber.
[0096] Second stage: While the preform is held above the crucible by an actuator, a vacuum is pulled on the chamber and a heating system preheats the preform to a temperature above 900°C and melts the aluminum. A high vacuum (1x10 -3 Up to 1x10 -9 Torr), but once the metal is melted and reaches 900°C, the vacuum quality will need to be reduced to a moderate vacuum (25 to 0.001 Torr), with the final value depending on the final holding temperature and the boiling points of the components in the melt.
[0097] Stage 3: When the chamber is under vacuum and both the preform shape and the aluminum bath are above 900°C, the preform is fully immersed in the liquid aluminum bath by an actuator.
[0098] Stage 4: Shortly after the shape is fully immersed in the liquid aluminum bath, a positive inert gas pressure is applied, and the temperature and pressure are kept constant until the displacement reaction is fully completed. Argon or helium can be used at pressures ranging from 0.3 MPa (50 psi) to 6.9 MPa (1000 psi) or higher.
[0099] Stage 5: When the chamber is under positive pressure, the shape is completely extracted from the liquid aluminum bath by actuators.
[0100] Stage Six: While the chamber is under positive pressure, the shape is allowed to cool.
[0101] Stage 7: Once the temperature of the shape drops below the solidification temperature of aluminum, the pressure in the VPT furnace is reduced to ambient atmospheric pressure, the chamber is opened, and the ceramic-metal composite shape is removed. This temperature is 660°C for pure aluminum and lower temperatures for aluminum alloys, depending on the alloying elements. The final composite has no centerline porosity, improving performance.
[0102] In a second preferred embodiment, the vacuum pressure converter does not include actuators to handle the preformed shape into or out of the liquid metal bath. Because this prevents the application of pressure after the shape is extracted from the bath, the shape must be run again in a second VPT furnace cycle. In this embodiment, the first VPT furnace cycle essentially consists of six stages.
[0103] First stage: a solid aluminum charge is loaded into a crucible, the preform shape is mounted in a fixture which is then placed on top of the solid aluminum, the entire assembly is loaded into a VPT furnace at ambient atmospheric pressure, and the chamber is then closed.
[0104] Second stage: A vacuum is pulled on the chamber and a heating system heats the preform shape and the aluminum to temperatures above 900°C. A high vacuum (1x10 -3 Up to 1x10 -9 Torr), but once the metal is melted and reaches 900°C, the vacuum quality will need to be reduced to a moderate vacuum (25 to 0.001 Torr), with the final value depending on the final holding temperature and the boiling points of the components in the melt.
[0105] Stage 3: When the chamber is under vacuum, the fixed preform is completely immersed in the liquid aluminum bath under the action of gravity as the aluminum melts. The melting temperature of the metal is 660°C for pure aluminum, or at lower temperatures for aluminum alloys, depending on the alloying elements.
[0106] Stage 4: Once the VPT furnace has reached a temperature above 900°C, a positive inert gas pressure is applied, and the temperature and pressure are kept constant until the displacement reaction is completely completed. Argon or helium can be used at pressures of 0.3 MPa (50 psi) to 6.9 MPa (1000 psi) or higher.
[0107] Stage 5: While the chamber is under positive pressure, the shape is allowed to cool to a temperature just above the solidification temperature of aluminum. Again, for pure aluminum, this temperature is above 660°C, or for aluminum alloys, this temperature is at a lower temperature.
[0108] Stage 6: While maintaining the VPT furnace temperature above the aluminum solidification temperature, the pressure in the chamber is reduced to ambient atmospheric pressure, the chamber is opened, the ceramic-metal composite shape is extracted from the liquid metal bath, and the crucible is removed from the furnace.
[0109] After the first VPT furnace cycle, the ceramic-metal shape must pass through a second VPT furnace cycle in order to eliminate the centerline porosity by remelting-repressurizing treatment. The second VPT furnace cycle basically consists of seven stages.
[0110] Stage 1: Load the composite shape into an empty VPT furnace at ambient atmospheric pressure and then close the chamber.
[0111] Stage 2: A vacuum is pulled on the chamber and the heating system begins to heat the composite shape. Medium vacuum (25 to 0.001 Torr) or high vacuum (1×10 -3 Up to 1×10 -9 (Trust).
[0112] Stage 3: Before the metal in the composite reaches its melting temperature, positive pressure is applied by using an inert gas (such as argon or helium). This temperature is 660°C for pure aluminum and lower temperatures for aluminum alloys, depending on the alloying elements. The inert gas can be used at pressures of 0.3 MPa (50 psi) to 6.9 MPa (1000 psi) or higher.
[0113] Stage 4: While applying positive inert gas pressure, a heating system raises the temperature of the shape to a point above the melting temperature of the metal in the composite.
[0114] Stage 5: When the chamber is under positive pressure, the temperature and pressure are kept constant until all pores are removed from the composite shape.
[0115] Stage Six: While the chamber is under positive pressure, the shape is allowed to cool.
[0116] Stage 7: Once the temperature of the shape drops below the solidification temperature of aluminum, the pressure in the VPT furnace is reduced to ambient atmospheric pressure, the chamber is opened, and the final ceramic-metal composite shape is removed. This temperature is 660°C for pure aluminum and lower temperatures for aluminum alloys, depending on the alloying elements. The final composite has no centerline porosity, improving performance.
[0117] The following are examples of these preferred embodiments of the invention.
[0118] Example 1: Conventional manufacture of a preformed test bar shape containing 36 wt% silicon dioxide (SiO2) and 64 wt% silicon carbide (SiC). The preform shape and a crucible containing an alloy of 80 wt% aluminum and 20 wt% silicon were loaded into a vacuum pressure converter. The VPT furnace was then closed and the chamber was pumped down to 1×10 -4The preform is held at a high vacuum of 5 torr. Under this negative pressure, the preform is held by an actuator above the crucible, and a heating system preheats the preform to a temperature of 900°C and melts the Al-Si alloy. When 900°C is reached, the vacuum is reduced to a moderate vacuum of 5 torr. Once both the preform shape and the aluminum alloy are heated to 1200°C, the preform is completely immersed in a liquid Al-Si bath by an actuator under this negative pressure. Shortly after the shape is completely immersed in the liquid metal bath, a positive inert argon pressure is applied. The temperature is maintained at 1200°C and the pressure is maintained at 5.0 MPa (725 psi) for 90 minutes. The transformation is completed during this time, reaching a rate of 8.5 mm per hour. While the chamber is maintained at this positive pressure, the shape is completely withdrawn from the liquid aluminum bath by an actuator and then allowed to cool to below 450°C. After the pressure in the VPT furnace is reduced to ambient atmospheric pressure, the chamber is opened and the SiC-Al 2 O 3 -Al ceramic-metal composite shapes. The flexural strength and apparent porosity of the test bars were measured according to ASTM standards C1161 and C20: the three-point flexural strength was 423 MPa (61,400 psi) and the apparent porosity was zero. The final composite did not pass the measurement of its density and similar Figure 2 and Figure 4 The structure shown defines the centerline pores.
[0119] Example 2: Two preform test bar shapes containing 36 wt% SiO2 and 64 wt% SiC were conventionally manufactured. The preform shape was mounted in a fixture and placed on top of a crucible containing a solid alloy containing 80 wt% Al and 20 wt% Si at room temperature. The crucible and fixture assembly was loaded into a vacuum pressure converter furnace. The VPT furnace was closed and a 1×10 -4 Torr of high vacuum.
[0120] Under this negative pressure, the preform and the Al-Si alloy are heated to a temperature of 900°C. At some point above 577°C, the molten aluminum alloy and the fixture and both preform shapes are completely immersed in the liquid metal bath by gravity. When 900°C is reached, the vacuum is reduced to a moderate vacuum of 5 Torr. Once the alloy bath reaches 1200°C, a positive pressure of inert argon gas of 7.0 MPa (1015 psi) is applied for 90 minutes. While the chamber is maintained at this positive pressure, the liquid metal is then cooled to 700°C or above its solidification temperature. At this point, the pressure in the VPT furnace is reduced to ambient atmospheric pressure, the chamber is opened, the fixture is extracted from the liquid metal bath, and the SiC-Al 2 O 3-Al ceramic-metal composite shape, and the crucible is removed from the furnace. One test bar is placed and remains intact while the second test bar is remelted and repressurized through a second VPT furnace cycle. The composite shape is loaded into the VPT furnace (after removing the crucible and metal) at ambient atmospheric pressure, and the chamber is closed. A 1×10 -4 A high vacuum of 100 torr is applied and the furnace then begins heating the composite shape. The negative pressure is maintained until the shape reaches 400°C, and then a positive pressure of 7.0 MPa (1015 psi) of inert argon is applied. Heating continues until the shape reaches 700°C, and then the test bar is held at that temperature for 90 minutes. While still maintained under positive pressure, the temperature of the shape is allowed to drop to 400°C. At this point, the pressure in the VPT furnace is reduced to ambient atmospheric pressure, the chamber is opened, and the final ceramic-metal composite shape is removed. The flexural strength and apparent porosity of the two test bars were measured in accordance with ASTM standards C1161 and c20. The test bar that passed only through the VPT furnace had a three-point flexural strength of 275 MPa (39,900 psi), an apparent porosity of 1.5% (volume), and a porosity of approximately 1.5% (volume). Figure 1 and Figure 3 In contrast, the test bars that were run through the VPT furnace twice had a three-point bend strength of 420 MPa (61,000 psi), zero apparent porosity as determined by density measurements, and no porosity similar to that seen in the Figure 2 and Figure 4 The centerline pores of the structure seen in .
[0121] Example 3: Conventional manufacture of a preform rod shape containing silicon dioxide (SiO2). The preform shape and a crucible containing commercially pure aluminum are loaded into a vacuum pressure converter. The VPT furnace is then closed and a high vacuum of 1×10-4 Torr is applied to the chamber. Under this negative pressure, the preform is held by an actuator above the crucible, and the heating system preheats the preform to a temperature of 900°C and melts the aluminum. When 900°C is reached, the vacuum is reduced to a medium vacuum of 5 Torr. Once both the preform shape and the aluminum alloy are heated to 1200°C, the preform is completely immersed in a liquid aluminum bath by an actuator under this negative pressure. Shortly after the shape is completely immersed in the liquid metal bath, an inert argon positive pressure is applied. The temperature is maintained at 1200°C and the pressure is maintained at 5.0 MPa (725 psi) for 90 minutes. While the chamber is maintained at this positive pressure, the shape is completely extracted from the liquid aluminum bath by an actuator and then cooled to below 600°C. After reducing the pressure in the VPT furnace to ambient atmospheric pressure, the chamber was opened and the Al 2 O 3 -Al ceramic-metal composite shape. The final composite had no centerline porosity as determined by density measurements.
[0122] Example 4: Conventional production of a preform rod shape containing SiO2. The preform shape and a crucible containing an alloy of 60 wt% aluminum and 40 wt% silver (Ag) were loaded into a vacuum pressure converter. The VPT furnace was then closed and a 1×10 -4 A high vacuum of 10 Torr is applied. At this negative pressure, the preform is held above the crucible by an actuator and a heating system preheats the preform to a temperature of 900°C and melts the aluminum alloy. When 900°C is reached, the vacuum is reduced to a moderate vacuum of 10 Torr. Once both the preform shape and the alloy are heated to 1200°C, the preform is completely immersed in a liquid Al-Ag bath by an actuator under this negative pressure. Shortly after the shape is completely immersed in the liquid metal bath, a positive pressure of inert argon gas is applied. The temperature is maintained at 1200°C and the pressure is maintained at 6.9 MPa (1000 psi) for 90 minutes. While the chamber is maintained at this positive pressure, the shape is completely withdrawn from the liquid aluminum alloy bath by an actuator and then allowed to cool to below 550°C. After the pressure in the VPT furnace is reduced to ambient atmospheric pressure, the chamber is opened and the Al 2 O 3 -Al-Ag ceramic-metal composite shape. The final composite had no centerline porosity as determined by density measurements.
[0123] Example 5: Conventional production of a preform rod shape containing SiO2. The preform shape and a crucible containing an alloy of 85 wt% aluminum and 15 wt% iron (Fe) were loaded into a vacuum pressure converter. The VPT furnace was then closed and a 1×10 -4 A high vacuum of 7.5 Torr is applied. At this negative pressure, the preform is held above the crucible by an actuator, and a heating system preheats the preform to a temperature of 900°C and melts the aluminum alloy. When 900°C is reached, the vacuum is reduced to a moderate vacuum of 7.5 Torr. Once both the preform shape and the alloy are heated to 1200°C, the preform is completely immersed in a liquid Al-Fe bath by an actuator under this negative pressure. Shortly after the shape is completely immersed in the liquid metal bath, a positive pressure of inert argon gas is applied. The temperature is maintained at 1200°C and the pressure is maintained at 5.0 MPa (725 psi) for 90 minutes. While the chamber is maintained at this positive pressure, the shape is completely withdrawn from the liquid aluminum alloy bath by an actuator and then allowed to cool to below 650°C. After the pressure in the VPT furnace is reduced to ambient atmospheric pressure, the chamber is opened and the Al 2 O 3 -Al-Fe ceramic-metal-intermetallic composite shape. The final composite had no centerline porosity as determined by density measurements.
Claims
1. A method for manufacturing a ceramic-metal composite material without centerline pores, characterized in that: The following steps are involved: a) Provide a vacuum pressure conversion (VPT) furnace, comprising: i) a chamber having an access door; ii) a crucible, the crucible being located in the chamber; iii) an inert gas source connected to the chamber, and a pressurizing system for selectively pressurizing the chamber with the inert gas; iv) a vacuum pump system connected to the chamber and selectively operable to evacuate the chamber; and v) a heating system operable to selectively heat the chamber; b) adding an aluminum charge to the crucible; c) placing a preform into the chamber above the crucible, the crucible being positioned on an actuator fixture, the preform having a non-enclosed side directly exposed to the interior of the chamber; d) operating the vacuum pump system to establish a partial vacuum within the chamber; e) operating the heating system under a partial vacuum state of the chamber to raise the chamber temperature to above 900 degrees Celsius, thereby melting the charge and heating the preform to the same temperature as the charge; f) operating the actuator to immerse the preform into the liquid aluminum in the crucible; g) operating the pressurization system to pressurize the chamber to a pressure greater than 50 psi with the inert gas selected from argon or helium; h) maintaining the temperature and pressure constant until the replacement reaction is completely completed; i) reducing the temperature in the chamber while maintaining a positive pressure in the chamber and operating the actuator to remove the current ceramic-metal composite shape from the crucible; j) allowing the composite shape to cool under positive pressure; and k) Removing the ceramic-metal composite shape from the cavity, the composite shape being free of centerline voids.
2. The method according to claim 1, characterized in that The step of operating the vacuum pump system includes first evacuating the chamber to a vacuum of 1×10 -3 Up to 1×10 -9 Torr until the aluminum in the crucible melts, and then increase the pressure to 0.001 to 25 Torr.
3. The method according to claim 1, characterized in that The process is carried out at a reaction rate of at least 8.5 mm / hour.
4. The method according to claim 1, characterized in that: The step of operating the pressurizing system includes pressurizing the chamber to a pressure of 50 to 1000 psi.
5. A method for manufacturing a non-porous ceramic-metal composite material, characterized in that: The following steps are involved: a) Provide a vacuum pressure conversion (VPT) furnace, comprising: i) a chamber having an access door; ii) a crucible, the crucible being located in the chamber; iii) an inert gas source connected to the chamber, and a pressurizing system for selectively pressurizing the chamber with the inert gas; iv) a vacuum pump system connected to the chamber and selectively operable to evacuate the chamber; and v) a heating system operable to selectively heat the chamber; b) adding a charge of aluminum or an aluminum alloy into the crucible; c) mounting a preform on a fixture and placing the preform into the chamber above the crucible; d) operating the vacuum pump system to establish a partial vacuum within the chamber; e) operating the heating system to raise the chamber temperature to above the melting point of the charge, thereby causing the charge to melt and the preform to be heated to the same temperature as the charge; f) when the chamber is in a vacuum state, when the charge melts, the preform is immersed in the molten charge in the crucible under the action of gravity; g) operating the pressurization system to pressurize the chamber with the inert gas to a pressure greater than 50 psi; h) maintaining the temperature and pressure constant until the replacement reaction is completely completed; i) reducing the temperature in the chamber while maintaining a positive pressure in the chamber and extracting a ceramic-metal composite shape above the melting point of aluminum from the crucible; j) allowing the composite shape to cool under positive pressure; k) removing the ceramic-metal composite shape from the chamber; l) removing the crucible from the chamber and reinserting the ceramic-metal composite shape into the chamber; m) the vacuum pump system is activated to reduce the chamber pressure to no greater than 25 Torr; n) heating the chamber to just below the melting point of the metal in the composite shape and activating the pressurization system to flow an inert gas into the chamber to a pressure of at least 50 psi; o) raising the chamber temperature to above the melting temperature of the metal in the composite shape; p) maintaining a constant temperature until all porosity is removed from the composite shape; q) cooling the composite shape within the chamber under positive pressure; and r) Removing the final ceramic-metal composite shape from the cavity.
6. The method according to claim 5, characterized in that In step b) a charge of aluminium is introduced into the crucible.
7. The method according to claim 5, characterized in that The inert gas is selected from argon or helium.
Citation Information
Patent Citations
Manufacture of articles from substances containing silica
US2702750A
Novel ceramic materials and methods for making same
US4713360A
Process for preparing ceramic-metal composite bodies
US5214011A
Ceramic / metal material and method for making same
US7267882B2
Method for performing silicon melt infiltration of ceramic matrix composites
CN1810727A